Pendampingan dan Pelatihan Pembuatan Cookies Berbasis Pangan Lokal Daun Kelor sebagai Upaya Pencegahan Stunting di Desa Bajar Sari - Lalu Abdurrahman Zulfan; Widya Astuti, Intan Rizki; Rasyid, Lalu Malik Fajar; Ranggawan, Mudiaman; Lestari, Widya; Zarafi, Raden Muhammad Zumar; Kamal, Rahmawati; Ibriyani, Maulina; Putri, Baiq Anggun Rizkia Cahya; Rosa, Nurita Zufia Abdina (Jurnal Wicara, 2025)
Stunting is a chronic nutritional problem that affects child growth and remains a priority health issue in Indonesia. Banjar Sari Village, located in Labuhan Haji District, East Lombok Regency, has the potential for local food resources such as moringa leaves (Moringa oleifera), which are rich in nutrients and can be utilized as an effort to prevent stunting. This community service activity aims to enhance the knowledge and skills of the community through assistance and training in the production of moringa leaf-based cookies as a local food initiative. The implementation methods include socialization, training, demonstration, discussion, assistance, product distribution, and evaluation. The results indicated an increase in community understanding regarding the importance of balanced nutrition and the utilization of moringa leaves in food processing. Participants successfully produced moringa leaf cookies independently and provided positive feedback on the products. The utilization of local food such as moringa leaves is expected to serve as a healthy alternative food to prevent stunting, while also creating home-based business opportunities for the residents of Banjar Sari Village.